2015
DOI: 10.1038/srep13129
|View full text |Cite
|
Sign up to set email alerts
|

Spatial correlations and optical properties in three-dimensional deterministic aperiodic structures

Abstract: Photonic systems have strongly varying optical properties depending on the spatial correlations present in a given realization. In photonic crystals the correlations are spatially periodic forming Bravais lattices whereas the building blocks of an amorphous medium are randomly distributed without any long-range order. In this manuscript we study the optical properties of so-called deterministic aperiodic structures which fill the gap between the aforementioned two limiting cases. Within this group we vary the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…[ 89 ] It is found that structures having this lattice spectral property show a transversal spread of light which is intermediate between that of pure-point and absolutely continuous lattices. [ 89 ] It is found that structures having this lattice spectral property show a transversal spread of light which is intermediate between that of pure-point and absolutely continuous lattices.…”
Section: Deterministic Aperiodic Structuresmentioning
confidence: 92%
See 1 more Smart Citation
“…[ 89 ] It is found that structures having this lattice spectral property show a transversal spread of light which is intermediate between that of pure-point and absolutely continuous lattices. [ 89 ] It is found that structures having this lattice spectral property show a transversal spread of light which is intermediate between that of pure-point and absolutely continuous lattices.…”
Section: Deterministic Aperiodic Structuresmentioning
confidence: 92%
“…In a following paper experimental studies are extended by including structures of singularly continuous lattice type. [ 89 ] It is found that structures having this lattice spectral property show a transversal spread of light which is intermediate between that of pure-point and absolutely continuous lattices. Compared with samples with a randomized arrangement of lattice sites, samples based on the absolutely continuous lattice type show stronger confi nement effects.…”
Section: Deterministic Aperiodic Structuresmentioning
confidence: 92%
“…Moreover, our generic approach for nanoengineered deterministic aperiodic lattices with rich Fourier spectra offers a great flexibility of optimization through tailoring their lattice geometry, basis shape, and spectral response range to match to the desired different thin film thicknesses, material of interest and for intended nanophotonic applications. The industrial application-viable and standard bottom-up fabrication technologies-compatible approach which we have demonstrated is envisaged to suit well for broadband integrated nanophotonic devices which demands large throughput and high resolution structured semiconductor materials with advanced tailorable features in nanoscale12345. Due to the inherent ability to boost broad band light matter interaction, the presented subwavelength scale deterministic nanophotonic lattices with precise tailorable structural features are envisaged to be appealing option for novel integrated nanophotonic applications2.…”
Section: Resultsmentioning
confidence: 99%
“…The dense Fourier spectra of such aperiodic lattice-embedded nanostructured materials could strongly modulate and enable flexible tailoring of the light-matter interaction for broad band nanophotonic applications in comparison to unstructured bulk materials1234. As the spatial correlations have very important impact on the optical properties of nanophotonic structures5, the correlated geometric distribution of nanophotonic lattice points in artificially structured semiconductor thin films could lead to more viable control on light in-coupling as well as light propagation within the semiconductor materials in comparison to its bulk counterpart. In order to ensure technological device practicability with industrial viability, together with the predictive models the specific structural engineering design approaches as well as high throughput large-area fabrication feasibility of high resolution subwavelength nanostructures are unavoidable and highly demanding26789.…”
mentioning
confidence: 99%
“…Photonic wave localization in a 3D icosahedral quasicrystal is carefully investigated by photonic wave transmission utilizing finite-difference methods. The diffusive transport and localization of photonic waves in the quasicrystal are revealed by widely accepted approaches 18,19 . We characterize the localization phenomena by analysing the spatial and temporal evolution of photonic waves.…”
mentioning
confidence: 99%